2021
DOI: 10.1111/ijlh.13687
|View full text |Cite
|
Sign up to set email alerts
|

Application of an optimized interpretation model in capillary hemoglobin electrophoresis for newborn thalassemia screening

Abstract: Introduction Newborn screening is an important supplement to thalassemia control and prevention. Capillary electrophoresis (CE) technology has several advantages for thalassemia screening but with low sensitivity, especially for thalassemia carriers. This study aims to illustrate the application of an optimized interpretation model in newborn thalassemia screening by capillary hemoglobin electrophoresis. Methods Two thousand, two hundred fifty‐eight neonates selected from four regions in China were enrolled an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 24 publications
(25 reference statements)
1
3
0
Order By: Relevance
“…As 100 α-thalassemia, 67 βthalassemia, and 152 healthy samples were analyzed in this work, some discrete data in Figure 3f are acceptable. In the electrophoresis process of chains of Hb, there are substantial significant differences obtained from β-thalassemia compared to α-thalassemia [35][36][37][38]. Therefore, by using a simple WT-ESI-MS method in this work, our results validated the results of the electrophoresis process of chains of Hb.…”
Section: Discussionsupporting
confidence: 73%
“…As 100 α-thalassemia, 67 βthalassemia, and 152 healthy samples were analyzed in this work, some discrete data in Figure 3f are acceptable. In the electrophoresis process of chains of Hb, there are substantial significant differences obtained from β-thalassemia compared to α-thalassemia [35][36][37][38]. Therefore, by using a simple WT-ESI-MS method in this work, our results validated the results of the electrophoresis process of chains of Hb.…”
Section: Discussionsupporting
confidence: 73%
“…The capillary electrophoresis has also been described as having a high diagnostic performance, as for example in an analysis of the performance of neonatal thalassemia screening by capillary electrophoresis in China for α-thalassemia and β-thalassemia, in which the optimized interpretation model found a sensitivity of 84.83% and a specificity of 99.14% for α-thalassemia and a sensitivity of 88.75% and a specificity of 98.73% for β – thalassemia. 23 …”
Section: Discussionmentioning
confidence: 99%
“…CE has found extensive applications in investigating the chemical structures and isoforms in various types of proteins, with a notable focus on Hb due to its crucial role in biological processes. Numerous CE-related studies have systematically explored the correlations between Hb’s variants, chemical modifications, and various pathological conditions, aiming to establish their significance as potential biomarkers. To determine a suitable method for detecting various Hb variants, a comparison was conducted among CE, cation-exchange HPLC, and matrix-assisted laser desorption ionization (MALDI) techniques using 1083 blood samples from southern China. The results showed that only the CE method was able to detect the 10 most prevalent Hb variants, making it the optimal instrument for this purpose …”
Section: Applicationsmentioning
confidence: 99%